Historical Comedy On Screen : Subverting History with Humour. - Salmi, Hannu (Intellect, 2011)
In 1893, Friedrich Engels branded history 'the cruelest goddess of all.' This sorrowful vision of the past is deeply rooted in the Western imagination, and history is thus presented as a joyless playground of inevitability rather than a droll world of possibilities. There are few places this is more evident than in historical cinema which tends to portray the past in a somber manner. Historical Comedy on Screen examines this tendency paying particular attention to the themes most difficult to laugh at and exploring the place where comical and historical storytelling intersect. The first schola.